SPIRITUAL AND MORAL DISORIENTATION IN THE CONTEMPORARY MARRIAGE - Aryana, I Gusti Made (International Conference on Cultural Studies, 2018)
This paper examined the contemporary marriage which lost sacred enthusiasm. The global upheaval through technology dissemination and lifestyle gave reflection to the new marriage ritual. The value and idea of Western secularism in the form of hedonism and consumerism successfully co-opt the meaning of marriage which is identical with local values. Holy, sacred and divine were not different with dirty, profane and worldly. All the values that are supposed to be distant and distinguished were dissolved and slushy in contemporary marriage practiced. Ultimately, the sacred ideal of marriage in the global era has a tendency to prioritize image and prestige, rather than essential.